1967
DOI: 10.1139/v67-502
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of thermal energy ions. VI. Hydrogen-transfer ion–molecule reactions involving polar molecules

Abstract: The rate constants for formation of the protonated molecule by ion–molecule reactions in CH3OH, (CH3)2O, and CH4 have been studied both at thermal energies and at 3.4 eV ion exit energy with a new mass spectrometer described in the present work. The rate constants are found to be approximately a factor of two greater than previously measured and it is concluded that an error in pressure measurement was made in the earlier work. Revised rate constants are presented for a number of systems studied previously. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(76 citation statements)
references
References 0 publications
3
73
0
Order By: Relevance
“…The pressure studies and the ratio plot studies reported below were carried out using the medium pressure instrument recently described (5). The pertinent operating conditions were a source temperature of approximately 100 "C, a primary ion travel distance of 0.54 cm, and a constant repeller field corresponding to 2.4 eV ion exit energy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure studies and the ratio plot studies reported below were carried out using the medium pressure instrument recently described (5). The pertinent operating conditions were a source temperature of approximately 100 "C, a primary ion travel distance of 0.54 cm, and a constant repeller field corresponding to 2.4 eV ion exit energy.…”
Section: Methodsmentioning
confidence: 99%
“…The pertinent operating conditions were a source temperature of approximately 100 "C, a primary ion travel distance of 0.54 cm, and a constant repeller field corresponding to 2.4 eV ion exit energy. The electron beam was pulsed and primary ion residence times were measured by the deflection technique previously described (5). The source pressures were measured directly with an MKS Baratron micromanometer.…”
Section: Methodsmentioning
confidence: 99%
“…diameter tubing to the ion-source. The pressure-dependent formation of CHs , which occurs in CH4 -CH4 collisions with a known specific reaction rate, indicated the pressure'readings to be accurate to within [9][10][11][12] t10%·…”
Section: Prefacementioning
confidence: 99%
“…Investigations of ion-molecule reactions in pure hydrogen sulfide [1][2][3][4][5][6] and methane [7][8][9][10][11][12][13][14][15] and also in the mixture of H 2 S with CH 4 were performed using various mass spectrometric techniques and methods [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%